2018
DOI: 10.1177/1526602818792854
|View full text |Cite
|
Sign up to set email alerts
|

Transradial Approach for Aortoiliac and Femoropopliteal Interventions: A Systematic Review and Meta-analysis

Abstract: Purpose: To present a systematic review and meta-analysis comparing the transradial approach for aortoiliac and femoropopliteal interventions to the traditional transfemoral access. Methods: A search of the public domain databases MEDLINE, SCOPUS, Web of Science, and Cochrane Library Databases was performed to identify studies related to the use of the transradial approach for infra-aortic procedures. Meta-analysis was used to compare the transradial to the transfemoral route in terms of procedure success, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…Furthermore, it is unclear how experienced the interventionists were regarding upper extremity access of any kind. This might be important as there is a clear learning curve in upper extremity access, as it is known for the transradial access [42]. All of these factors influence the external validity of our findings.…”
Section: Limitations and Quality Of Evidencementioning
confidence: 84%
“…Furthermore, it is unclear how experienced the interventionists were regarding upper extremity access of any kind. This might be important as there is a clear learning curve in upper extremity access, as it is known for the transradial access [42]. All of these factors influence the external validity of our findings.…”
Section: Limitations and Quality Of Evidencementioning
confidence: 84%
“…A meta-analysis of radial and femoral access in infra-aortic interventions, using a maximum sheath size of 6-8.5 French, reported significantly fewer complications when radial access was used (OR 0.25, 95% CI 0.07-0.86). 102 A metaanalysis of hepatic artery interventions in patients with primary or secondary liver malignancy reported no differences in access-site-related outcomes of radial and femoral access, but did show a patient preference for radial access. 103 Based on extensive experience with femoral access, the still limited evidence supporting radial access, and the substantial complication rate of brachial access, the preferred entry site for PMAS is currently femoral, followed by (left) brachial or radial, but is primarily dependent on the expertise of the operator.…”
Section: Pmasmentioning
confidence: 99%
“…In the article by Meertens et al, 1 the hospital length of stay was not statistically lower in TRA patients, and the radiation burden with the 2 accesses was similar. The operator working on lower extremity arteries via a TFA is very near the x-ray source.…”
Section: Tra For Lower Extremity Interventionsmentioning
confidence: 83%
“…The meta-analysis by Meertens et al 1 reported a need for a second access in about 10% of TRA procedures, which may appear as a limitation. However, if the transradial strategy fails, injections from this access can be used to better guide a femoral puncture and subsequent retrograde navigation of guidewires and also a more precise positioning of balloons and stents.…”
Section: Tra For Lower Extremity Interventionsmentioning
confidence: 99%